Insight into Antifungal Metabolites from Bacillus stercoris 92p Against Banana Cordana Leaf Spot Caused by Neocordana musae - Qunfang Yu; Pengbo He; Yanxiang Qi; Pengfei He; Ayesha Ahmed; Xin Zhang; He Zhang; Yixin Wu; Shahzad Munir; Yueqiu He (Biomolecules)
Banana crop ranks among the most crucial fruit and food crops in tropical and subtropical areas. Despite advancements in production technology, diseases such as cordana leaf spot, caused by Neocordana musae, remain a significant challenge, reducing productivity and quality. Traditional chemical controls are becoming less effective due to the development of resistance in target pathogens, which pose significant environmental and health concerns. Consequently, there is growing attention toward the development of biocontrol strategies. Here, we identified a new bacterial strain, Bacillus stercoris 92p, from the rhizosphere soil of banana. We evaluated its ability to suppress the growth of N. musae and other fungal pathogens that cause leaf spot disease in bananas. The inhibitory effect of B. stercoris 92p were checked using dual culture assays, microscopic observations, and pot experiments. Furthermore, the biocontrol mechanisms were investigated using whole-genome sequencing and biochemical analyses. The results showed that B. stercoris 92p exhibited significant antifungal activity against N. musae and other fungal pathogens, with inhibition rates exceeding 70%. Microscopic examination revealed significant morphological alterations in the hyphae and conidia of the tested pathogens. In pot experiments, B. stercoris 92p effectively reduced the severity of cordana leaf spot, achieving a biocontrol efficacy of 61.55%. Genomic analysis and biochemical tests indicated that B. stercoris 92p produces various antifungal compounds, including lipopeptides (fengycins and surfactins), hydrolytic enzymes (proteases and amylases), and phosphate-solubilizing metabolites. In conclusion, the study highlights that B. stercoris could potentially be used as a potential biological control agent against cordana leaf spot.